CAPABILITIES OF THE SERVICE OF MANPOWER AND TRANSMIGRATION IN REDUCING THE UNEMPLOYMENT RATE IN SUKABUMI DISTRICT - Saskia Zahra; Rizki Hegia Sampurna; Dine Meigawati (DIA: Jurnal Administrasi Publik, 2024)
This research is entitled "Capability of the Department of Manpower and Transmigration in Reducing Unemployment in Sukabumi Regency". This study aims to determine the capability of the Manpower and Transmigration Office in reducing unemployment in Sukabumi District. The method used in this research is descriptive qualitative method. The theory used in this study uses Kumalasari's theory (2014: 48) there are 4 dimensions of institutional, human resources, financial and technical. Data collection techniques in this study are observation, interviews and documentation studies. The informants in this study were employees of the Sukabumi Regency Manpower and Transmigration Office. The results in this study indicate that the Sukabumi Regency Manpower and Transmigration Office has not been said to be capable in the program to reduce the number of unemployed in Sukabumi Regency. Of the four indicators used, there are two indicators that have not been carried out optimally, namely the human resources indicator, financial indicators.